The coding manual for qualitative researchers - Saldana, Johnny (SAGE, 2013)
An in-depth guide to each of the multiple approaches available for coding qualitative data. In total, 32 different approaches to coding are covered, ranging in complexity from beginner to advanced level and covering the full range of types of qualitative data from interview transcripts to field notes.